Practice Audit in Gastroenterology (Page) Program: A Novel Approach to Continuing Professional Development - David Armstrong; Roger Hollingworth; Tara Gardiner; Michael Klassen; Wendy Smith; Richard H Hunt; Alan Barkun; Michael Gould; Desmond Leddin (Canadian Journal of Gastroenterology)
BACKGROUND: Practice audit is an important component of continuing professional development that may more readily be undertaken if it were less complex. This qualitative study assessed the use of personal digital assistants to facilitate data collection and review.